Prediction modelling the financial distress using corporate governance indicators in Indonesia - Irdha Yusra; Novyandri Taufik Bahtera (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2021)
We examine whether the indicators of company governance procedures are associated with the risk of bankruptcy or financial distress in Indonesia. An empirical study we conducted using a causal model of corporate governance indicators in forecasting financial distress. The data used in this study is panel data. Using samples from assembling companies registered on the Indonesia Stock Exchange during the 2017-2019 period, we obtained as many as 105 observations selected by the purposive sampling method. Our results indicate that financial distress can be predicted by corporate governance mechanisms, although statistically it is only proven by a few indicators in our study. Specifically, our results demonstrate that institutional ownership, managerial ownership, and independent commissioners do not affect financial distress. Furthermore, our study shows evidence of a significant influence between the size of the board of directors and audit committee on financial distress. Our interpretation is that research on financial distress prediction models using corporate governance indicators has provided empirical evidence.